2010
DOI: 10.1103/physrevb.82.075134
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform site-charge distribution and fluctuations of charge order in the metallic state ofα(BEDT-TTF)2I3

Abstract: We present the site-charge distribution in the charge-ordered and metallic states of ␣-͑BEDT-TTF͒ 2 I 3 , based on the assignment of the C v C stretching modes 2 , 3 , and 27 of ␣-͑BEDT-TTF͒ 2 I 3 with the aid of 13 C-and deuterium-substituted compounds. The nonuniform site charges in both the metallic and insulating phases were consistent with those determined by a recent x-ray diffraction study. Comparing the line shapes of the chargesensitive vibrational modes of ␣-͑BEDT-TTF͒ 2 I 3 with those of isostructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 44 publications
12
74
0
Order By: Relevance
“…Yue et al, showed that the linewidth of metallic α-I 3 is about two to three times as large as that of α-NH 4 Hg [130]. As shown in Figure 21a, the linewidth of ν 27 of α-I 3 is much broader than the charge-insensitive mode such as the CH 2 bending mode.…”
Section: Fluctuation Of Charge Order In Metallic Phasementioning
confidence: 88%
See 3 more Smart Citations
“…Yue et al, showed that the linewidth of metallic α-I 3 is about two to three times as large as that of α-NH 4 Hg [130]. As shown in Figure 21a, the linewidth of ν 27 of α-I 3 is much broader than the charge-insensitive mode such as the CH 2 bending mode.…”
Section: Fluctuation Of Charge Order In Metallic Phasementioning
confidence: 88%
“…Recently, Alemany et al, pointed out that the hydrogen bond between the ethylene groups of BEDT-TTF and I 3 − plays an essential role in the CO transition of α-I 3 [129]. In the MI transition of α-I 3 , Raman [111] and infrared [130] spectra showed drastic changes as seen in Figure 18. The assignment of these bands along with vibronic bands was conducted with the aid of 13 C and deuterium substituted compounds.…”
Section: α-(Bedt-ttf) 2 I 3 and Related Compoundsmentioning
confidence: 91%
See 2 more Smart Citations
“…Salt with another packing arrangement, α-(BEDT-TTF) 2 X and θ-(BEDT-TTF) 2 X, has been a topic of interest due to the metal-insulator (MI) transition and charge disproportionation by off-site coulomb interaction [22][23][24][25][26][27][28][29]. In this type of organic conductor, various charge disproportionation patterns are realized, and these patterns give important information about the electronic structure.…”
Section: Introductionmentioning
confidence: 99%